PENGELOLAAN PASAR LILUWO OLEH DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA GORONTALO - Rian Hepat, Adisti Putri; Rachman, Ellys; Antu, Yahya (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2024)
This study aims to determine the management of the liluwo market by the Gorontalo City Trade and Industry Service. The research method used is descriptive qualitative. The results of the study concluded that the management of the liluwo market by the Gorontalo City Trade and Industry Service is not optimal. This can be seen from the aspect of the planning of the arrangement of the liluwo market which is not good, which can be seen from the inadequate trader facilities. From the aspect of coordination between the Trade and Industry Service and traders, it is still very low, this can be seen from the lack of coordination or consultation between the Trade and Industry Service and traders so that there is a delay in paying dues. From the aspect of supervision of security officers in regulating the Gorontalo City liluwo market which has been carried out has not been effective, this can be seen from the absence of officers who always stay in the security supervision of the Gorontalo City liluwo market.